2021
DOI: 10.1002/adfm.202009419
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Plasmonic Color Filters Enable Direct Optical Imaging of Ion Implantation in Thin Films

Abstract: Optical metamaterials offer precise control over the properties and interactions of light at the nanoscale, attracting interest in many new fields of research including chemical and molecular sensing, magnetic antennas, and photovoltaic elements. By utilizing the phenomenon of extraordinary optical transmission (EOT) plasmonic devices enable the detection of minute changes in the local, near‐surface, dielectric properties of materials, opening up a wide range of different applications. Characterization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…For example, in the present application, the periodicity of the aperture spacing was 400 nm in one direction (referred to here as the transverse electric or TE mode) and 500 nm in the orthogonal direction (referred to here as the transverse magnetic or TM mode) 7 . By fabricating the apertures in a rectangular array, the device output and sensitivities vary significantly with the incident polarisation vector [8][9][10][11] . Both the structure and nanofabrication of these plasmonically active microscope slides have been described in previous publications (e.g.…”
Section: Plasmonically Active Microscope Slidesmentioning
confidence: 99%
“…For example, in the present application, the periodicity of the aperture spacing was 400 nm in one direction (referred to here as the transverse electric or TE mode) and 500 nm in the orthogonal direction (referred to here as the transverse magnetic or TM mode) 7 . By fabricating the apertures in a rectangular array, the device output and sensitivities vary significantly with the incident polarisation vector [8][9][10][11] . Both the structure and nanofabrication of these plasmonically active microscope slides have been described in previous publications (e.g.…”
Section: Plasmonically Active Microscope Slidesmentioning
confidence: 99%
“…The colorimetric histology device is a nanofabricated microscopy slide that exploits the extreme sensitivity of surface plasmon resonance (SPR) to convert subtle changes in the local optical properties of samples adhered to the device surface into a striking colour contrast. In previous work using well- characterised analytes as well as thin films of varying dielectric constant, we showed that bimodal plasmonic devices combined with linearly polarised incident light can be tuned to maximise the sensitivity to certain analytes [43, 44]. Bimodal plasmonic devices also exhibit extreme sensitivity to changes in the local birefringence properties of the sample which manifests as a colour change on the slide.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, arrays based on circular or square-shaped holes have been the most studied [25,[28][29][30], but the advances in nanofabrication techniques have provided the means for the realization of metal nanohole arrays of complex shapes [31,32]. As a matter of fact, it has been shown that non-circular shaped holes dramatically influence the optical properties, generating polarization-dependent behaviors and paving the way for advanced sensing applications [18,[33][34][35]. Gordon et al [36,37] experimentally studied the optical response of a square array of elliptical holes with different aspect ratios, observing strong polarization selectivity.…”
Section: Introductionmentioning
confidence: 99%